Édouard Manet’s painting as unintelligibility that interpellates - Gutiérrez-Jordano, Carmen (situArte, 2023)
The aim of this article is to show that Manet conceived painting as an interpellation of the painting to the spectator. In order to methodologically justify this thesis, we have used several procedures. The first has been to analyze the pictorial context in which Manet’s work is produced. The second has been to understand the two dominant ways of understanding painting until then: theatrical painting, totally exposed and open to the public, and absorptive painting, closed in on itself, as if there were no public. The third is to expose Manet’s own position. Manet avoids those two traditional perspectives and considers that painting can only be an interpellation if it paints the invisible and, above all, if it paints scenes that represent moments that are not immediately comprehensible. Then painting will consist of a confrontation between the painting and the spectator.